The importance of the work of cooperativist education to rural extension - Palloma Ferreira , Rosa; Presno Amodeo, Nora Beatriz; Neves de Sousa, Diego (Cooperativismo & Desarrollo, 2013)
The cooperativist education is the learning process that goes beyond mere speeches and proposals and values, similarly, the social and business side and the specific demands of the training of organizations and partners. Regarding agricultural cooperatives, the training demands correspond to actions directed to rural producers. This study is done in order to analyze the contribution of cooperative education tools to the rural extension and describe the relationship of cooperative education and performance of the Empresa de Asistencia y Extensión Rural of the Department of Minas Gerais. Methodologically, it was used for exploratory research and for the technique of the questionnaire sent to 452 agricultural cooperatives throughout 2011 and 2012. Among the results is evidenced that the development of cooperative education works done by organizations has been shown as extension jobs providing benefits to cooperatives looking to daily make viable the guidance and training received.